[PP.10.15] PREVALENCE OF SEXUAL DYSFUNCTION IN FEMALES WITH RESISTANT HYPERTENSION. (September 2016) - Imprialos, K.; Stavropoulos, K.; Boutari, C.; Kokkinos, P.; Pittaras, A.; Faselis, C.; Petidis, K.; Deligkaris, P.; Stavropoulos, N.; Athyros, V.; Karagiannis, A.; Doumas, M.
Abstract : Objective: Sexual dysfunction is common in females with essential hypertension. The prevalence of sexual dysfunction in females with resistant hypertension has yet to be investigated. The objective of our study was to assess the incidence of sexual dysfunction in females with resistant hypertension. Design and method: Our study included 109 sequential patients presenting with resistant hypertension in our hypertension outpatient clinic. Sexual function was assessed using the Female Sexual Function Index (FSFI) and sexual dysfunction was defined as FSFI scores below 25.5. Resistant hypertension was defined according to current guidelines as blood pressure >140/90 mmHg, despite the administration of at least three antihypertensive medications in maximum tolerated dose, including a diuretic. Results: The majority of the patients had either known cardiovascular disease (28/109, 26%) or additional cardiovascular risk factors (52/109, 48%). Study participants were on three drugs (32/109. 29%), four drugs (63/109. 58%), or five or more antihypertensive drugs (14/109, 13%). No female patient had ever been questioned about her sexual function in the past. Sexual dysfunction was found in 78 out of 109 (72%) female patients participating in the study. Conclusions: Sexual dysfunction is very often in women with resistant hypertension. Lack of diagnosis in daily practice is due to lack of relevant questions, highlighting the need to inform attending physicians about this under-recognized medical condition.